The Evaluation of Processes of Bankruptcy in Ukraine in the Aspect of the Development of Controlling at the Enterprise (Economic journal of Lesya Ukrainka Volyn National University, 2015)
In the making of market economy in Ukraine many enterprises appeared in the crisis state. This is due to the influence of the unstable environment and inadequate behavior of most business entities, which ultimately leads to bankruptcy. The article discusses the economic substance of the concept of bankruptcy. As an economic phenomenon bankruptcy directly associated with a reduction in its effectiveness. The study found that over thepast 14 years, the share of unprofitable business entities in the economy was at least a third. The reasons for a sufficiently high number of loss-making entities operating in Ukraineʼs economy. The combination of negative factors such as tax and administrative burden of objective economic circumstances forced entrepreneurs go into the shadows or massively suspend activities, business freeze until better times. Revealed that during the period the largestnumber of unprofitable enterprises account for 2013. The report states that, the indexes with which to display the intensity and scale of the processes of bankruptcy. For the calculation of these indicators and the analysis of activity of the Institute of bankruptcy in Ukraineʼs economy, the estimation of its operation, the estimation of its operations under the World Bank «Doing Business 2014».Directions improve the performance of business entities. Revealed that one of the important factors to help you reduce the number of bankrupt enterprises is to respect the proper performance of the tasks of controlling service. The necessity of improving the application of the measures to prevent bankruptcy.
Keywords: bankruptcy, liquidity, efficiency, financial rehabilitation, financial crisis, controlling